Organic amendments for mitigating soil salinity in rice - Chowdhury, Shithi; Bhusan, Dhiman; Hashem, Md Abul; Hoque, Md Anamul (Research in Agriculture Livestock and Fisheries, 2019)
Salinity causes cellular damage and limits crop productivity. Accumulation of organic compound is one of the adaptive mechanisms to salinity in plants. The experiments were laid out in a randomized complete block design with three replications at the farmer’s field of Botiaghata, Khulna to investigate the mitigating effects of organic manures on salinity stress in rice genotypes during both aman and boro seasons. Two T. aman rice (salt-sensitive; BR-23 and local cultivar; Mohini) and two boro rice (salt-sensitive; BRRI dhan-29 and salt-tolerant; BINA dhan-8) were used as test crops. Farmyard manure (FYM) and poultry manure (PM) were applied to the soils during final land preparation. There were five treatments namely T0= control (no manure), T1=FYM (5 t/ha), T2=FYM (10 t/ha), T3=PM (4 t/ha), T4=PM (8 t/ha).Thirtyday- old rice seedlings were transplanted in the experimental plots. Salinity caused a significant reduction in growth and yield of both aman and boro rice. Under saline condition, BR-23 (aman rice) produced higher yield than local cultivar Mohini in aman season while BINA dhan-8 produced higher yield than BRRI dhan29 in boro season. Soil amendments with FYM and PM significantly increased the growth, and grain and straw yields of all rice cultivars under saline conditions. Increased nutrient uptake and K+/Na+ ratio in rice were also observed due to application of organic manures. No considerable changes in post-harvest soil properties such as pH, EC, CEC and organic matter status of saline soils were observed by addition of FYM and PM. The present study suggests that soil amendments with FYM and PM improve salt tolerance in rice by increasing K+/Na+ ratio and nutrient uptake. Res. Agric., Livest. Fish.6(1): 11-17, April 2019